The Role of Perceived Convenience and Trust in Sustainability Claims in Driving Sustainable Purchasing Behaviour in E-Commerce Users - Adhika Ramadhan; Novia Purnamasari; Martin Agusta; Herman S. Soegoto; Lilis Puspitawati (Golden Ratio of Mapping Idea and Literature Format, 2026)
Growing public awareness of environmental problems has boosted demand for sustainable shopping, especially on e commerce platforms that often highlight green or eco friendly labels in their marketing. However, many consumers doubt these claims because they do not fully trust the information provided. Past studies usually looked at convenience and trust as separate factors. Few have combined them to see how they work together in online shopping, particularly in developing nations like Indonesia. This research tries to fill that gap. It looks at how perceived convenience—meaning easy navigation, quick checkout, and clear product information—and trust in sustainability claims affect whether people actually buy green products. The study used a quantitative method, collecting data from 143 e commerce users chosen through purposive sampling. Participants answered a Likert scale questionnaire, and the researchers analyzed the data using SEM PLS. The findings show that convenience has a strong, positive effect on sustainable buying Behaviour. When platforms are user friendly, shoppers are more likely to choose eco friendly items. Trust in the sustainability claims also matters a lot. If shoppers believe the claims are honest and transparent, they are more willing to buy sustainable products. Moreover, trust acts as a bridge: it makes the influence of convenience even stronger, because a convenient platform that also provides believable green information encourages more purchases. Despite positive results, the study points out a common problem—there is still a gap between what consumers say they intend to do and what they actually do when it comes to buying environmentally friendly goods online.